2022
DOI: 10.13057/biodiv/d230223
|View full text |Cite
|
Sign up to set email alerts
|

The potential of endophytic bacteria to suppress bacterial leaf blight in rice plants

Abstract: Abstract. Rahma H, Nurbailis, Busniah M, Kristina N, Larasati Y. 2021. The potential of endophytic bacteria to suppress bacterial leaf blight in rice plants. Biodiversitas 23: 775-782. Endophytic bacteria are potential as biocontrol agents against bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae in rice to support sustainable agriculture. This study aimed to select and characterize 22 endophytic bacteria isolated from healthy rice, determine their ability to promote plant growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Furthermore, Faisal 116 demonstrated that Ochrobactrum intermedium and Bacillus cereus enhanced the growth, root and shoot length, weight and quantity of seeds per pod, and number and value of grains per plant of Lens esculenta. Taken together, it is suggested that Ochrobactrum isolates could improve plant growth by promoting nutrient uptake, participating in symbiotic nitrogen fixation, and preventing plant diseases in Acacia mangium 117 , tea 118 , cucumber 119 , and mung bean 120 . The PGPR strains had variable effects for improving the growth, physiology, yield and nutrient uptake of wheat under controlled and natural soil conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Faisal 116 demonstrated that Ochrobactrum intermedium and Bacillus cereus enhanced the growth, root and shoot length, weight and quantity of seeds per pod, and number and value of grains per plant of Lens esculenta. Taken together, it is suggested that Ochrobactrum isolates could improve plant growth by promoting nutrient uptake, participating in symbiotic nitrogen fixation, and preventing plant diseases in Acacia mangium 117 , tea 118 , cucumber 119 , and mung bean 120 . The PGPR strains had variable effects for improving the growth, physiology, yield and nutrient uptake of wheat under controlled and natural soil conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Penyakit hawar daun bakteri yang disebabkan oleh bakteri Xanthomonas orysae pv oryzae (Xoo) merupakan penyakit utama pada tanaman padi. Luas areal tanaman padi di Indonesia yang terserang Xanthomonas oryzae mencapai 26.998 ha (Direktorat Perlindungan Tanaman Pangan, 2019); (Rahma et al, 2022). Menurut Nuyanto, 2018; Carsono et al, 2021), kehilangan hasil akibat serangan penyakit Hawar Daun Bakteri (HDB) sekitar 15-24%.…”
Section: Pendahuluanunclassified
“…Upaya pengendalian yang telah digunakan selama ini umumnya menggunakan pestisida, namun belum efektif karena harganya mahal dan menimbulkan pencemaran bahan kimia pada lingkungan. Pengendalian dengan menggunakan agen hayati seperti mikroorganisme endofit yang berada pada tanam padi (Rahma et al, 2022). Cendawan endofit merupakan salah satu mikroba yang memiliki potensi sebagai agen hayati untuk pengendalian penyakit hawar daun bakteri.…”
Section: Pendahuluanunclassified
“…The use of beneficial microorganisms for plants has emerged as an effective tool for controlling diseases (Ozaktan et al 2012;Rahma et al 2022). Endophytic plant growth-promoting bacteria (PGPB) may benefit plant growth by controlling phytopathogens and/or producing bio-stimulating substances, helping plants to cope with stress conditions.…”
Section: Introductionmentioning
confidence: 99%